DOCTORS DIFFER: A PHILOSOPHICAL PERSPECTIVE - Bhoi, Kamala Kant (International Journal of Research -GRANTHAALAYAH, 2025)
The phrase "Drs differ" acknowledges the inherent uncertainty and variability in medical practice. This paper explores the complexities of medical decision-making through two case studies, highlighting the importance of patient-centered care and the need for nuanced understanding of medical knowledge.